Estimating the execution time of fully-online multiscale numerical simulations - Fabian, Juan; Gomes, Antônio; Ogasawara, Eduardo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2020: Anais do XXI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2020.14069, 2020)
In this paper, we propose a methodology for estimating the execution time of simulations driven by multiscale numerical methods. The methodology explores the idiosyncrasies of multiscale simulators to reduce the uncertainty of predictions. We use the multiscale hybrid-mixed (MHM) ﬁnite element method to validate our methodology. We compare our proposed technique with prediction models automatically selected and calibrated by Auto-WEKA. We show that the models obtained with our technique are competitive when compared with the models coming from Auto-WEKA, being interpretable and with much less computational effort during the learning process.